Urinary Tract Infection Diagnosis and Response to Therapy in Long-Term Care: A Prospective Observational Study - Peter Daley; Carla Penney; Susan Wakeham; Glenda Compton; Aaron McKim; Judy O’Keefe; Brendan Barrett; Lindsay Nicolle (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: The prevalence of asymptomatic bacteriuria among residents of long-term care (LTC) facilities is high, and is a source of inappropriate antibiotic prescription.